2009
DOI: 10.1057/hsq.2009.15
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate analysis of infant death in England and Wales in 2005–06, with focus on socio-economic status and deprivation

Abstract: Current health inequality targets include the goal of reducing the differential in infant mortality between social groups. This article reports on a multivariate analysis of risk factors for infant mortality, with specific focus on deprivation and socio-economic status. Data on all singleton live births in England and Wales in 2005-06 were used and deprivation quintile (Carstairs index) was assigned to each birth using postcode at birth registration. Deprivation had a strong independent effect on infant mortal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 4 publications
(4 reference statements)
2
38
0
2
Order By: Relevance
“…Approximately a quarter of all infant deaths in England and Wales would potentially be prevented if all babies were born in circumstances as favourable as the least deprived families 51. Supportive family policy can help protect children from the damaging effects of poverty and inequality.…”
Section: What Can Be Done To Strengthen Conditions For Children In Brmentioning
confidence: 99%
“…Approximately a quarter of all infant deaths in England and Wales would potentially be prevented if all babies were born in circumstances as favourable as the least deprived families 51. Supportive family policy can help protect children from the damaging effects of poverty and inequality.…”
Section: What Can Be Done To Strengthen Conditions For Children In Brmentioning
confidence: 99%
“…Difficulties in describing and recording infant ethnicity have been recognised as ethnicity is a self-defined concept, which makes its use in infants and other populations unable to self-report problematic. Previous studies have used infant ethnicity,16 maternal ethnicity,17 maternal country of birth17 and composite variables,16 combining infant and maternal descriptors to try and overcome the limitation of the non-availability of self-report in this population.…”
Section: Discussionmentioning
confidence: 99%
“…20,30,41,42 Research had shown an increasing risk of non-chromosomal anomalies with increasing deprivation, in contrast to a decreasing risk of chromosomal anomalies. 43 This last finding was predominantly a result of the increased risk of chromosomal anomalies with increasing maternal age.…”
Section: Socioeconomic Inequalities In Deaths Associated With Congenimentioning
confidence: 99%